Clinical Study of Symptomatic Nonacute Intracranial Large Arterial Occlusion with Endovascular Recanalization - Dan, Bitang; Zhu, Bifeng; Zeng, Wei; Peng, Tao; Liu, Jing; Li, Xin; Zhang, Junjian (Journal of Neurological Surgery Part B: Skull Base, 2023)
Objectives This study reported a single-center clinical trial of endovascular treatment for symptomatic nonacute occlusion of the intracranial large artery (NA-ILAO). The aim of this study was to evaluate the safety, feasibility, and clinical effect of simple balloon dilatation and stent implantation.Methods The patients diagnosed with symptomatic NA-ILAO were enrolled. A total of 40 cases were included in this study. While recanalization failed in 4 patients, it was successful in 36 patients, who were then divided into two groups for further analysis: balloon dilatation group (n = 24) and stent implantation group (n = 12). The perioperative complications, clinical outcome, and follow-up results were analyzed.Results Perioperative complications in the stent implantation group were significantly higher than those in the simple balloon dilatation group (p < 0.05). There were 21 and 10 cases of 90-day good clinical outcome (modified Rankin scale [mRS] ≤ 2) in the balloon and stent groups, respectively (p = 0.518). All patients with successful recanalization underwent digital subtraction angiography (DSA) or CT angiography (CTA) during an average follow-up of 14 months. There were two cases of restenosis in the balloon dilatation group and one in the stent implantation group (p = 1.000). There were two cases of re-occlusion in the stent group and none in the balloon dilatation group (p < 0.001). Stroke recurred in two cases in the stent group and in one case in the simple balloon dilatation group (p = 0.013).Conclusion Endovascular recanalization is safe and feasible for patients with symptomatic NA-ILAO. Compared with stent implantation, simple balloon dilation may be a better recanalization method, but larger randomized controlled trials are needed to confirm it.
Keywords: nonacute intracranial large artery occlusion; endovascular recanalization; balloon dilatation; stent implantation